Fully implicit numerical integration of the Yoshida-Uemori two-surface plasticity model with isotropic hardening stagnation - Riccardo Fincato; Seiichiro Tsutsumi; Alex Zilio; Gianluca Mazzucco; Valentina Salomoni (Fracture and Structural Integrity)
The paper deals with the numerical investigation and implementation of the two-surface plasticity model (or bounding surface model). This plasticity theory allows to describe the deformation behavior under large strain cyclic plasticity and the material stress-strain responses at small-scale re-yielding after large pre-straining. A novel strategy to model the isotropic hardening stagnation is developed within a fully implicit integration scheme in order to speed up the computation and to improve the material description.